Quantifying the Geomorphology of the Drainage Basins Along the Greater Khingan Mountains in NE China - Lin, Lingling; Li, Xuemei; Ma, Zifa (Frontiers in Earth Science, 2021)
Drainage basins are fundamental elements of the earth’s surface, and quantifying their geomorphic features is essential to understand the interaction between tectonics, climatic, and surface processes. In this study, 40 basins of the Greater Khingan Mountains were selected for hypsometric analysis using a 90-m Shuttle Radar Topography Mission digital elevation model. The hypsometric integral values range from 0.13 to 0.44, with an average value of 0.30, and most hypsometric curves exhibit remarkable downward concave shapes. This feature indicates that most drainage basins and the landscape of the Greater Khingan Mountains are approaching the old-age development stage, consistent with the present moderately stable tectonic activity. The spatial distribution of the χ values is characterized by unambiguously higher values on the western flank than those on the eastern flank in the middle and southern segments of the Greater Khingan Mountains. We interpret this as an indicator of the disequilibrium across the main divide. The interpolation of the erosion rates and channel steepness for the catchments on both sides of the Greater Khingan Mountains revealed westward divide migration, which is consistent with the lower χ values, a higher slope, and local relief observed along the eastern flanks. Considering the long-term tectonic evolution pattern between the Greater Khingan Mountains and Songliao Basin, the landscape decay and slow westward divide migration were mostly driven by the inherited Cenozoic tectonics and precipitation gradient across East Asia.